Styrylpyrylium Salts: H1 and C13 NMR High-Resolution Spectroscopy (1D and 2D). (2nd June 2010) - Ouédraogo, Jean Claude W.; Tapsoba, Edouard; Sib, Sié Faustin; Bonzi-Coulibaly, Yvonne Libona
Abstract : H 1 andC 13 NMR high-resolution spectroscopy (1D and 2D) (H 1, H 1 -COSY, HSQC, HMBC) for four styrylpyrylium perchlorates were carried out and signal attributions are reported. Chemical shifts observed onC 13 NMR spectra for the styrylpyrylium salts were compared with net atomic charge for carbon obtained by AM1 semiempirical calculations. The position of the styryl group present low effect on chemical shifts for carbon atoms, while the presence of methyl group led to the unshielding of the substituted carbon.